Reasoning COVID-19: the use of spatial metaphor in times of a crisis - Kremer, Dominik; Felgenhauer, Tilo (Humanities and Social Sciences Communications, 2022)
As other crises before, the COVID-19 pandemic put established discursive routines at stake. By framing the pandemic as a crisis, an immediate search for adequate counter-measures started to define proper means of mitigation and protection for the population. In the early stages of COVID-19, when little reliable information on the virus and its transmission behaviour was available, an intense use of metaphor to explain and govern the crisis had to be expected. Beside its well-known impact on (geo-)politics, a thorough analysis especially of the use of spatial metaphors to reason about the crises is still missing. In our approach, we rely on the foundational work of Lakoff and Johnson (1980) on image schemata, and prior work on spatial metaphors as part of argumentation patterns from cultural geography (Schlottmann, 2008). After a thorough analysis of prominent examples according to the argumentation scheme of Toulmin (1976 [1958]), we explored examples from the pre-existing corpus on COVID-19, deliberately compiled by DWDS for analysis of language patterns used throughout the pandemic. In a subsequent filter-refinement approach building on methods from cognitive linguistics and utilising a chunk of the same corpus, we were able to obtain and discuss results on the variety of spatial metaphors used at that time.
CRIS-Team Scopus Importer:2022-08-19